2019
DOI: 10.1021/acs.jpcc.9b07684
|View full text |Cite
|
Sign up to set email alerts
|

Design Strategies for High-Efficiency Ratiometric Two-Photon-Excited Fluorescent and Room-Temperature Phosphorescent Probes for Hypochlorous Acid

Abstract: Hypochlorous acid (HOCL) plays a critical role in the natural defense system, but excessive production of HOCL leads to many diseases. It is very essential to monitor the distribution and level of endogenous HOCL. However, the applicable two-photon-excited fluorescent (TPEF) and phosphorescent probes for biological imaging and quantitative detection is rare due to low efficiency and vague mechanism. Therefore, we thoroughly researched the electron structures and luminous mechanisms of turn-on and ratiometric T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…The same TD-B3LYP level was adopted for the TPA simulations, which has been shown to give consistent TPA cross sections with the experimental trends for various large chromophores. 41,[50][51][52][53] The accurate description of double excitations deserves future investigations. [32][33][34] All the above calculations were performed in the Gaussian 16 54 package, except for the TPA simulation performed in the Dalton 55,56 program.…”
Section: Computational Detailsmentioning
confidence: 99%
“…The same TD-B3LYP level was adopted for the TPA simulations, which has been shown to give consistent TPA cross sections with the experimental trends for various large chromophores. 41,[50][51][52][53] The accurate description of double excitations deserves future investigations. [32][33][34] All the above calculations were performed in the Gaussian 16 54 package, except for the TPA simulation performed in the Dalton 55,56 program.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Apart from electron donors and acceptors, isomerism also plays an important role in TPA [34][35][36][37] and fluorescence. 38,39 It is well known that the fluorescence quantum yield (0.13) of phenanthrene is lower than that (0.30) of anthracene. 40 They found that a benzo[h]coumarin derivative exhibited high fluorescence quantum yield (0.37), while its corresponding benzo[ f ]coumarin derivative induced fluorescence quenching (0.08).…”
Section: Introductionmentioning
confidence: 99%
“…Apart from electron donors and acceptors, isomerism also plays an important role in TPA 34–37 and fluorescence. 38,39 It is well known that the fluorescence quantum yield (0.13) of phenanthrene is lower than that (0.30) of anthracene. 40 Hao et al recently designed a series of benzocoumarin-based fluorescent probes for H 2 O 2 detection.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the reaction product (DCM-OH) also possesses a two-photon absorption feature. To date, most of the fluorescent probes still are one-photon excited with a relatively shorter excitation wavelength, and thus the inevitable interference of background fluorescence and shallow depth of tissue penetration limit their application in living systems. In contrast, two-photon excited fluorescent (TPEF) probes, simultaneously absorbing two photons with low energy, have the advantages of deep tissue penetration, high spatial resolution, and less photodamage to tissues. But the practical application of the TPEF probe leaves much to be desired, due to their rather small two-photon absorption (TPA) efficiency and unclear internal mechanisms. Therefore, it is still necessary to research and develop a novel TPEF probe with large TPA cross section and high luminous efficiency.…”
Section: Introductionmentioning
confidence: 99%